Design and implementation of a 2D circular domain seismic tomography general ray tracer algorithm - Imhof, Armando Luis; Calvo, Carlos Adolfo (Ingenieria y Desarrollo, 2014)
Tomographic matrix inversion techniques in travel time are based on the construction of distance matrices containing information of survey array geometry, the discretized domain shape and the distance traveled by rays in each area elements that compose it. The domain considered is generally rectangular for ease of geometric resolution. In this work is circular due to the need to carry out investigation in columns of this shape. Distance matrices are used to solve the linear system, which leads to the determination of velocity values in each element of the domain. Taking in mind discretization, there are several possibilities for the construction of arrays of pixels: may those be defined in one quadrant and obtaining the rest by symmetry; build arrays with uniform pixels using the previous strategy, and finally to be independent from quadrant and generate any distribution and individual size thereof. Each option will provide access to new research possibilities. In this work an original procedure was developed for the construction of matrices with elements of the last type. The procedure was validated with simulated data using the SVD method, which demonstrated the efficiency of the algorithm.